2015
DOI: 10.1038/hr.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the QT interval duration in hypertension with antihypertensive treatment

Abstract: The duration of the QT interval as measured by 12-lead electrocardiography is a measure of myocardial repolarization and is widely used to describe cardiac abnormalities, to determine the presence of cardiac toxicity and to evaluate drug safety. In hypertension, the QT interval is a predictor of the risk of both coronary events and cardiovascular death, after adjusting for the effects of additional risk factors. The mechanism of QT interval prolongation is multifactorial and includes cardiomyocyte hypertrophy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 141 publications
(162 reference statements)
3
19
2
Order By: Relevance
“…Thus, QTc dispersion prolongation is often observed in people with hypertension and obesity. Previous studies showed that blood pressure control and weight loss were effective for improving ventricular repolarization abnormality [10,11]. In the present study, treatment with an SGLT2 inhibitor significantly reduced systolic blood pressure and body weight.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Thus, QTc dispersion prolongation is often observed in people with hypertension and obesity. Previous studies showed that blood pressure control and weight loss were effective for improving ventricular repolarization abnormality [10,11]. In the present study, treatment with an SGLT2 inhibitor significantly reduced systolic blood pressure and body weight.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies showed that blood pressure control and weight loss were effective for improving ventricular repolarization abnormality [10,11]. Previous studies showed that blood pressure control and weight loss were effective for improving ventricular repolarization abnormality [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…QT interval is a predictor of the risk of both coronary events and cardiovascular death after adjusting for the effects of additional risk factors in hypertension [30, 31]. QT intervals in HD patients are longer than those in the general population, and 65% of these patients show longer QT intervals [32].…”
Section: Discussionmentioning
confidence: 99%